The Analysis of Relationship Between Compensation and Work Motivation of Teachers in Islamic Education Institution. - Musran Munizu; Siti Aisyah Hanim; Arwin Arwin; Helmi Ali; Abdurohi Abdurohi (Departement of Mathematics Education, 2023)
The purpose of this research is to ascertain whether there is a relationship between pay and job motivation in teachers, how much of a contribution is made, and whether this relationship is significant or not. Descriptive-quantitative research methodology was adopted in this study. While a questionnaire was used to collect data for this study. Using product moment correlation analysis, data is processed. Because 0.882 was between 0.70-0.90 and the correlation coefficient significance test indicated that the r-table was at a 5% significance level of 0.514, rxy = 0.882 was included in the product moment correlation interpretation table with strong or high interpretation results. In other words, Ho is rejected and Ha is accepted, with a contribution level of 77.4%, as it can be shown that r-count is bigger than r-table at a significance level of 5%. So, there is a very strong and important link between teacher motivation and compensation.